PENGEMBANGAN APLIKASI FRONT END SISTEM LAPORAN KERUSAKAN INTERN PDAM KOTA DENPASAR - Pidada, Ida Bagus Naradhipa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2018)
PDAM Denpasar City is a Government-Owned Business Entity, which provides services to the community, especially in an effort to fulfill the basic needs of the community for healthy drinking water. Most of the systems available in PDAM Kota Denpasar are still done manually, only payments have been made online. Based on this reason the author conducted the XV period Job Training (PKL) in 2018 in PDAM Kota Denpasar because this agency needed something more in order to be able to keep up with this online and advanced development.From PDAM programmers and field supervisors, they advise the authors to make an application or website for an internal damage report system, because in the PDE section they often respond to complaints manually and also so that other field employees who are damaged do not need to come to the PDE to file complaints, an application / website. Based on this reason the author decided to make an internal damage report system application. The focus of the author this time is on the Front end of the internal damage report system. Based on the observation of the writer in PDAM Kota Denpasar, there are three types of complaints, which are then categorized by the authors, namely Software, Hardware, and Network. Later other field employees can determine the category / type and write down the details of the complaint.Keywords: Damage Reports, Website, Information